ARTIFICIAL INTELLIGENCE: A NEW TREND IN VISUAL EFFECTS (VFX) - Sharma, Hitesh; Kochhar, Khyati (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Stories have been told by humans for many years. Stories that are written down or spoken can be imagined to a certain level, but visual effects (VFX) are needed to make an imagined story come to life through motion. When using Visual Effects (VFX) in a movie or other digital media, one can create or change the background, add actors, characters, or creatures, remove or cover objects and change the actors themselves. In fact, there has been a noticeable advancement in the field of visual effects (VFX) due to artificial intelligence (AI), indicating a new trend in the sector. By streamlining procedures, offering insightful data, and opening up previously unexplored possibilities, artificial intelligence (AI) has the potential to completely transform a number of industries. Although there are adjustments and fears associated with artificial intelligence's integration into the visual effects (VFX) industry, the effect on employment is a complicated matter that needs to be carefully considered. Even so, worries about job displacement are legitimate. Looking to the future, Artificial Intelligence (AI) development is growing. Automated Rotoscoping and Masking, Facial Recognition and Animation (Deepfakes), Scene Reconstruction and Enhancement, Realistic CGI Characters, Content Creation and Augmentation, Predictive Analytics for Production Planning, Deep Learning for Image Processing, Real-time VFX, Customized Content Creation has brought significant advancements to the VFX industry. This study explores the potential uses of Artificial Intelligence (AI) in the field of Visual Effects. How difficult or complex tasks will be completed in a different way to reduce production time and increase effectiveness or cost-effectiveness, with the possibility that the majority of the current visual effects workflows may eventually be replaced. Will it be possible for people outside of the Visual Effects industry to produce high-caliber film effects in the future if AI technology becomes more widely available? This investigation poses the following query: How will artificial intelligence affect the visual effects sector? Keywords: Artificial Intelligence, CGI, VFX, Cinematic, Technology, Filmmaking, Indian Cinema, Digital Media